The Shift in Governance Through the Fall of Sound in the Face of Image: From Homo Sapiens to Homo Vidiens: A Panoptic Perspective in Alfred Hitchcock's Cinema within the Context of Media Political Economy: The Case of Rear Window - KANTAR, Gökmen; Akova, Sibel (International Journal of Contemporary Economics and Administrative Sciences, 2025)
When examined within the framework of social sciences, the phenomenon of surveillance—most precisely defined as systematic observation—refers to the monitoring of all actions and behaviors undertaken by individuals, groups, and societies within the context of their vital processes, particularly communication practices. According to numerous theorists across various disciplines within the social sciences, surveillance functions as a critical tool for collecting, recording, and controlling data essential to the establishment and maintenance of governance systems and authority. Surveillance, enabling states to consolidate their power and frequently regarded as an instrument reinforcing this power, encompasses not only the oversight of behaviors exhibited by individuals and societies within national borders but also the recording, organization, protection, and regulation of the gathered data. This administrative element constitutes a significant area of investigation within the field of media political economy. The increasing complexity and evolution of administrative practices in contemporary societies—driven by factors such as communication, transportation, infrastructure, technology, globalization, and digitization—are rendered feasible through mechanisms of surveillance. The phenomenon of surveillance, forming the central focus of this study, is a pivotal subject of our time and represents the foundational basis of media political economy. Analyzing the historical development of media as a communication tool reveals that the governance changes resulting from the ascendancy of image over sound have profoundly and pervasively shaped the lives of contemporary societies. Within the trajectory of human history, spanning from Homo Sapiens to Homo Vidiens, the transformation and evolution of media political economy can be most distinctly observed in the cinema of Alfred Hitchcock. This study endeavors to analyze Hitchcock’s cinema through a panoptic perspective. Specifically, it investigates the panoptic viewpoint in Hitchcock’s Rear Window within the framework of media political economy, aiming to elucidate the governance shifts induced by these transformations.